Does exchange rate variability affect bilateral export volume in CARICOM - Straughn, Ryan (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Examines the effect of real exchange rate variability on bilateral exports between Barbados, Jamaica and Trinidad and Tobago using annual data for varying periods between 1954 and 2001.